An Analysis of Mandarin Imperative Sentences in the Drama 'The Untamed' Episode 1 by Mo Xiang Tong Xiu - Fadhilah, Dian Nur; Pamuji, Dian Yuni; Siregar, Sheyra Silvia (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This study aims to analyze the types and functions of imperative sentences found in episode 1 of the Chinese drama The Untamed, adapted from the novel Mo Dao Zu Shi by Mo Xiang Tong Xiu. Using a descriptive qualitative method, the research focuses on identifying imperative forms in the characters' utterances and classifying them into five categories: command, prohibition, request, invitation, and permission. The data were collected through non-participatory observation and documentation, then analyzed using imperative sentence theory in Mandarin. The findings show a total of 94 imperative sentences, with directive imperatives being the most dominant (52 instances), followed by prohibitions (18), invitations (6), requests (6), and indirect imperatives (9). These variations not only reflect the linguistic structure but also reveal the characters’ emotions, social relations, and power dynamics. The study highlights how Mandarin imperative sentences in popular media can serve as a valuable resource in understanding communication strategies, pragmatic functions, and sociocultural context in language use.